Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Review - Page 904: 2


$(f - g)(x)=-(x+6)$

Work Step by Step

If $f(x) = x-5$ and $g(x)= 2x+1$ $(f - g)(x)=f(x) - g(x) = x-5 - (2x+1) = x-5-2x-1=-x-6=-(x+6)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.